Managing talent retention - Phillips, Jack J.
Retention is becoming one of the most pressing concerns of employers worldwide. This book provides an overview of talent retention and defines retention and turnover in very specific measures. It explores the full impact of talent departure and most important it offers proven solutions to talent retention. The book clearly shows how to forecast the ROI of talent retention solutions and how to capture the actual ROI after the solution was implemented. This is a practical book providing an ROI approach to HR managers and practitioners